Morphological and molecular identification of specimens in the genus Euseius (Acari: Phytoseiidae) from the Republic of Congo - Okassa, Mireille Belle Mbou; Ntabi, Dollon Mbama; Lenga, Arsene (Zootaxa, 2020)
The purpose of this study was to identify the taxonomic status of several individuals belonging to the genus Euseius, collected from three host plants (cassava, okra, and chilli) in the Republic of the Congo, using morphometric and molecular analysis. For this, hierarchical ascending classification on principal component analysis was performed using morphological measurements from 21 and 22 individuals of E. fustis and Euseius sp., respectively, with the original description of Euseius neodossei considered. For molecular analysis, two DNA fragments were amplified and sequenced: the mitochondrial 12S rRNA and the nuclear ribosomal region ITSS. This integrative approach found that (1) morphological differences existed between the Euseius sp. and both E. neodossei and E. fustis, and (2) both mitochondrial DNA fragments showed a clear delineation between Euseius sp. and E. fustis. The results obtained highlight the value of using integrative taxonomy to improve the identification of species in under-sampled areas and the need to increase the number of DNA sequences deposited in GenBank database from this region. This is the first time that DNA sequences of mites from the Congo (Brazzaville) have been deposited in this database.